Costs and effects of telerehabilitation in neurological and cardiological diseases: A systematic review - Del Pino, Rocio; Díez-Cirarda, Maria; Ustarroz-Aguirre, Iker; Gonzalez-Larragan, Susana; Caprino, Massimo; Busnatu, Stefan; Gand, Kai; Schlieter, Hannes; Gabilondo, Iñigo; Gómez-Esteban, Juan Carlos (Frontiers in Medicine, 2022)
Introduction Telerehabilitation in neurological and cardiological diseases is an alternative rehabilitation that improves the quality of life and health conditions of patients and enhances the accessibility to health care. However, despite the reported benefits of telerehabilitation, it is necessary to study its impact on the healthcare system. Methods The systematic review aims to investigate the costs and results of telerehabilitation in neurological and cardiological diseases. MEDLINE and EMBASE databases were searched from 2005 to 2021, for studies that assess the costs and results of telerehabilitation compared to traditional rehabilitation (center-based programs) in neurological and cardiological diseases. A narrative synthesis of results was carried out. Results A total of 8 studies (865 participants) of 430 records were included. Three studies were related to the costs and results of telerehabilitation in neurological diseases (specifically in stroke). In total, five studies assessed telerehabilitation in cardiological diseases (chronic heart failure, coronary heart disease, acute coronary syndrome, and cardiovascular diseases). The duration of the telerehabilitation ranged from 6 to 48 weeks. The studies included cost-analysis, cost-benefit, cost-effectiveness, or cost-utility. In total, four studies found significant cost/savings per person between 565.66 and 2,352.00 (p < 0.05). In contrast, most studies found differences in costs and clinical effects between the telerehabilitation performed and the rehabilitation performed at the clinic. Just one study found quality-adjusted life years (QALY) significant differences between groups [Incremental cost-effectiveness ratio (ICER) per QALY (−21,666.41/QALY). Discussion Telerehabilitation is an excellent alternative to traditional center rehabilitation, which increases the accessibility to rehabilitation to more people, either due to the geographical situation of the patients or the limitations of the health systems. Telerehabilitation seems to be as clinical and cost-effective as traditional rehabilitation, even if, generally, telerehabilitation is less costly. More research is needed to evaluate health-related quality of life and cost-effectiveness in other neurological diseases. Systematic review registration [<ext-link ext-link-type="uri" xlink:href="https://figshare.com/articles/journal_contribution/Review_Protocol_Costs_and_effects_of_Telerehabilitation_in_Neurological_and_Cardiological_Diseases_A_Systematic_Review/19619838" xmlns:xlink="http://www.w3.org/1999/xlink">https://figshare.com/articles/journal_ contribution/Review_Protocol_Costs_and_effects_of_Telerehabilitation_in_ Neurological_and_Cardiological_Diseases_A_Systematic_Review/19619838], identifier [19619838].